On Invariant Speed of Light - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
A new physical model of the appearance of light, properties, and its trajectory. Explains the paradox of invariance and isotropy of light based on the laws of classical physics.